2009
DOI: 10.1061/(asce)gt.1943-5606.0000099
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Spatial Variability on Slope Reliability Using 2-D Random Fields

Abstract: The paper investigates the probability of failure of slopes using both traditional and more advanced probabilistic analysis tools. The advanced method, called the random finite-element method, uses elastoplasticity in a finite-element model combined with random field theory in a Monte-Carlo framework. The traditional method, called the first-order reliability method, computes a reliability index which is the shortest distance ͑in units of directional equivalent standard deviations͒ from the equivalent mean-val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
134
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 461 publications
(152 citation statements)
references
References 36 publications
1
134
0
7
Order By: Relevance
“…We conveniently assumed constant values of the strength parameters in all of our numerical simulations. This approach ignores spatial variabilities in c 0 and / 0 [11], and may lead to inadequate characterization of the stability of hillslopes during rainfall events [8,14]. Nevertheless, the use of constant strength parameters simplifies investigations into the impact of bedrock depth uncertainty and/or soil hydraulic uncertainty in slope stability studies.…”
Section: Strength Parametersmentioning
confidence: 99%
See 3 more Smart Citations
“…We conveniently assumed constant values of the strength parameters in all of our numerical simulations. This approach ignores spatial variabilities in c 0 and / 0 [11], and may lead to inadequate characterization of the stability of hillslopes during rainfall events [8,14]. Nevertheless, the use of constant strength parameters simplifies investigations into the impact of bedrock depth uncertainty and/or soil hydraulic uncertainty in slope stability studies.…”
Section: Strength Parametersmentioning
confidence: 99%
“…As hillslope interiors are costly, labor-intensive, and difficult to access, most slope stability studies use a relatively simple description of the bedrock surface [3,6,7,11]. Resulting topographic maps often do not do justice to complex field measurements of the bedrock depth, which often demonstrate significant spatial variability [3,33] with a geometry that is difficult to characterize adequately with some closed-form mathematical expression, while hydraulic and strength parameters can vary abruptly at the soil-bedrock interface.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the uncertain material properties tend to vary in space, even within homogeneous layers. Several studies have shown that the spatial variability of the soil has an important influence on the computed reliability [5][6][7]. An accurate representation of the spatial variability of the uncertain soil material properties requires a random field modelling.…”
Section: Introductionmentioning
confidence: 99%